THE RETROSPECTIVE ANALYSIS OF THE TSARIST RUSSIA CRIMINAL LAW ON RESPONSIBILITY FOR CRIMES IN THE SPHERE OF JUSTICE (by Regulation On criminal and executive punishments of 1845 and Criminal Regulation of 1903.) - A. Kurakov (Russian Journal of Economics and Law)
The article studies the issue of formation of the Russian criminal law on crimes against justice. The author shows the continuity of some legal decisions on the responsibility for encroachment of justice according to the Tsarist Russia law and to the modern Russian criminal law.